Study on accident propagation ability of chemical industry park based on mixture degree decomposition algorithm and accident propagation probability. Issue 3 (22nd December 2020) - Wang, Zheng; Hu, Yiyi; Yang, Yanxia; Dong, Ran; Song, Yuanjin; Jia, Xiaoping; Wang, Fang
Abstract: In order to better characterize the accident propagation mechanism in chemical industry park (CIP), a method combining mixed degree decomposition (MDD) algorithm with accident propagation probability is proposed to measure the accident propagation ability of nodes in the accident chain network of CIP in this paper. First, the accident chain network model of CIP is established by using complex network theory and the nodes in the network model are layered according to the accident propagation ability based on the MDD algorithm. Second, the accident propagation probability value of each node in the network is defined and calculated according to the characteristic factors of the node itself. Finally, the result of MDD algorithm is combined with the accident propagation probability value by using Euclidean distance formula, the nodes with strong accident propagation ability in the accident chain network of CIP are determined. The case analysis shows that the method has higher discrimination, can effectively measure the accident propagation ability of nodes in the accident chain network of CIP, and better identify the nodes with strong propagation ability.